The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1365-2249.1999.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

In situexpression of B7 and CD40 costimulatory molecules by normal human lung macrophages and epithelioid cells in tuberculoid granulomas

Abstract: SUMMARYNormal alveolar macrophages (AM) are not efficient in inducing the proliferation of resting T lymphocytes, and, rather, tend to inhibit pulmonary immune responses. In contrast, epithelioid cells (EC), activated macrophages that play an essential role in the course of granulomatous responses, appear to stimulate T cell proliferation efficiently. The inability of macrophages to deliver potent costimulatory signals through the B7/CD28 and CD40/CD40L pathways could explain their weak accessory cell activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
3
15
1
Order By: Relevance
“…The cellular composition of granulomas in CD40L Ϫ/Ϫ mice indicated that recruitment of both CD4 ϩ and CD8 ϩ T cells is altered. Although previous immunohistochemical studies have shown that human tuberculoid granulomatous lesions contain readily detectable levels of B7-1 and B7-2 on epithelioid cells and of CD28 on T cells (42), our data indicated that CD28 is dispensable for protective granulomatous responses against BCG in a murine model. T cells from CD28-deficient mice have reduced expression of IL-2 receptor ␣(IL-2R␣), reduced T-helper cell function, and reduced proliferation to concanavalin A but are still able to mount an effective anti-lymphocytic choriomeningitis virus cytolytic immune response in vivo (40).…”
Section: Discussioncontrasting
confidence: 90%
“…The cellular composition of granulomas in CD40L Ϫ/Ϫ mice indicated that recruitment of both CD4 ϩ and CD8 ϩ T cells is altered. Although previous immunohistochemical studies have shown that human tuberculoid granulomatous lesions contain readily detectable levels of B7-1 and B7-2 on epithelioid cells and of CD28 on T cells (42), our data indicated that CD28 is dispensable for protective granulomatous responses against BCG in a murine model. T cells from CD28-deficient mice have reduced expression of IL-2 receptor ␣(IL-2R␣), reduced T-helper cell function, and reduced proliferation to concanavalin A but are still able to mount an effective anti-lymphocytic choriomeningitis virus cytolytic immune response in vivo (40).…”
Section: Discussioncontrasting
confidence: 90%
“…However, when antigen-pulsed EC surrogates were tested for their ability to prime T lymphocytes in vivo, these cells were more efficient in this function when compared with control macrophages. This result corroborates the assumption that in a granuloma environment ECs may be activating T lymphocytes effectively [19].…”
Section: Discussionsupporting
confidence: 90%
“…a 0 min ¼ no incubation at 37 C. The presence of costimulatory and adhesion molecules on ECs and/or multinucleated giant cells in granulomas found in infectious [17,19] or autoimmune [18] diseases suggests that antigen presentation takes place in these lesions. Moreover, it has been described that ECs express costimulatory molecules like CD80 (B7-1), CD86 (B7-2) and CD40, which were found in close contact with T lymphocytes in tuberculoid and sarcoid lesions [19]. We have previously shown that EC surrogates express MHC class II [14] and in this report we extended this knowledge, showing that these cells express other molecules involved in antigen presentation such as B7-2, CD40 and CD54 (ICAM-1).…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the earliest human in vivo results to confirm the prior reports on murine TB (22,37). In one other study of costimulatory molecules in human TB, Soler et al (38) failed to show differences in the expression of CD80/CD86 costimulatory molecules in tubercle granulomas caused by M. tuberculosis. This finding is in apparent contrast to our current findings.…”
Section: A B Csupporting
confidence: 79%